O papel do design gráfico num projeto curatorial de arte contemporânea - Forte, Raquel Monteiro (2020)
Exhibitions can be perceived as a communication medium which conveys the message that the curator wants to transmit. Essentially, it is a tool that helps in the mediation between the art and the public. The definition of curatorship wasn’t always clear and has been suffering changes over the time. For example, artistic institutions, in order to refresh their image and at the same time stay updated to evolution of the world around them, use new strategies and methods to transmit their thoughts and concepts. To establish these dialogues they rely on the cura-tor’s essential participation who uses a wide range of tools to make this function effective. Thereby, the graphic design is, many times, considered as a privileged medium of curatorship for the expositive content’s framing and organization, con-voking information systems and communication strategies that help the curator show his message to the public. This master dissertation starts from the evolution of contemporary art, the chang-ing perspective of the museum’s role, the big transformations of the curator’s role and, finally, the recent introduction of the graphic designer in curatorial projects of contemporary art, particularly focusing on the Do outro lado do espelho exhi-bition, exposed at the Calouste Gulbenkian Foundation, since the end of 2017 until early 2018, and also the exhibition O Fotógrafo Acidental: Serialismo e Ex-perimentação em Portugal, 1968-1980, exposed at Culturgest in 2017.